PERCEPATAN TANAH MAKSIMUM DAERAH MANOKWARI BERDASARKAN TINJAUAN KASUS-KASUS GEMPABUMI - Richard Lewerissa (Jurnal Natural, 2009)
The research aimed to determine a Peak Ground Acceleration in manokwari based on Earthquakes cases from 1900 to 2006 using empirical earthquakes formula. This studi was finished at center of meteorology and geophysical agency in Jayapura Papua during September 2008. Result of Mcguirre dan Donovan method shown that in south manokwari have a maximum Peak Ground Acceleration in the amount 448,82 gal to 618 gal. While in north of manokwari have a intermediate peak gruond acceleration in the amount 100 gal to 125 gal. This research describable a temporary simple empirical study so that needed to advance reseacrh about Peak Ground Acceleration in region of manokwari regarding to survei of geology and stratigrafy condition in manokwari